Disconnecting trapdoors: Phylogenomic analyses reveal evolutionary contrasts in trapdoor spiders with intercontinental distribution (Idiopidae, Idiopinae) - Fonseca-Ferreira, R. [UNESP]; Derkarabetian, S.; Morales, M. J.A.; Opatova, V.; Belintani, T. [UNESP]; Lyle, R.; Guadanucci, J. P.L. [UNESP] (Elsevier, 2025)
Among Mygalomorphae spiders, the family Idiopidae is the second most diverse, consisting exclusively of trapdoor spiders and is divided into three subfamilies: Arbanitinae, Genysinae, and Idiopinae. The subfamily Idiopinae, distinguished mainly by anterior lateral eyes that project forward, includes 153 species across seven genera, distributed throughout South America, Africa, and parts of Asia. Within this subfamily, the genus Idiops includes the greatest diversity and is the only genus recorded in both the New and Old Worlds. Utilizing a taxon set from the Neotropical and Afrotropical regions, with specimens collected from 1947 to 2021, our study provides the first phylogenomic analysis of the family based on Ultraconserved Elements (UCEs). To assess the monophyly of Idiopinae and Idiops, as well as the relationships among genera within the subfamily, we conducted phylogenetic analyses employing maximum likelihood, Bayesian inference, and coalescent-based methods. The phylogenetic trees reveal that Idiopinae forms a monophyletic lineage, split into two geographically distinct groups: one with African species and the other with Neotropical species. We did not recover monophyly of the genus Idiops; Neotropical Idiops form a monophyletic lineage, while African Idiops species group with Titanidiops, forming a sister lineage to the remaining African Idiopinae. The relationship between the phylogenetic results obtained and the main morphological differences observed among the genera is discussed. Finally, our study challenges the monophyly of Idiopidae by including Neocteniza, which is found to be an independent lineage sister to Ctenizidae and the rest of Idiopidae.
Keywords: Afrotropical species; Idiops; Mygalomorphae; Neocteniza; Neotropical species; Ultraconserved Elements